2010
DOI: 10.4149/km_2010_2_137
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive weld bonding of interstitial free steel at spot welding for automotive application

Abstract: In this study, the effect of adhesive bonding on strength and strength-ductility behaviour of welding joint in electrical resistance spot welding of 7315 grade IF steel sheets was investigated. 7315 grade (DIN EN 10130-1999) IF steels were adhesively bonded and different welding current and welding cycle conditions were performed in welding process. For adhesive bonding, Loctite Terostat 9120-Grey and Terostat 9220-Black grade adhesive bonders were used. Additionally, adhesively bonded joint samples were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
0
9
0
1
Order By: Relevance
“…The hardness values decrease gradually from the base metal to the HAZ/base metal interfacial region as a result of internal strain energy being relieved due to weld heat input. Martensitic transformation may occur in the HAZ that is exposed to heat and in the weld metal that is exposed to melting and solidification for a short time [12] and nugget formation depends on many variables, but the welding heat input is probably the most effective parameter [14].…”
Section: Resultsmentioning
confidence: 99%
“…The hardness values decrease gradually from the base metal to the HAZ/base metal interfacial region as a result of internal strain energy being relieved due to weld heat input. Martensitic transformation may occur in the HAZ that is exposed to heat and in the weld metal that is exposed to melting and solidification for a short time [12] and nugget formation depends on many variables, but the welding heat input is probably the most effective parameter [14].…”
Section: Resultsmentioning
confidence: 99%
“…The nearest thing to ductility measurement is the hardness test since the hardness of metal is usually an indication of its ductility [21]. 13 shows the effect of welding current on the microhardness of the galvanized steel observed at the currents of 23,600 A and 26,800 A. Hardness rose from the base metal towards the center of the weld where the maximum hardness was reached.…”
Section: Hardnessmentioning
confidence: 99%
“…Many researchers have studied spot welding process by experimental and numerical techniques in order to increase the quality of products [6]. Hardness is one of the most important factors that affect spot weld quality [7]. The weld nugget or fusion zone (FZ) (which is melted during welding process and is resolidified showing a cast structure) provides the highest hardness values, and this is followed by the heat-affected zone (HAZ) (which is not melted but undergoes microstructural changes) and base metal (BM) [4].…”
Section: Resistance Spot Weldingmentioning
confidence: 99%
“…Also, it is reported that the pearlite-ferrite microstructure is harder than ferrite microstructure [9]. Generally, grain coarsening was observed at the weld nugget and HAZ of spot-welded samples [7].…”
Section: Resistance Spot Weldingmentioning
confidence: 99%